Multiscale reaction model coupling dual-site microkinetics with bulk diffusion and CFD–DEM for a perovskite oxygen carrier - Wang, Ruiwen; Li, Zhenshan; Liu, Lei (Frontiers in Chemistry, 2025)
Non-catalytic heterogeneous reactions in fluidized beds involve physical and chemical processes spanning across the atom, surface, grain, particle, and reactor scales. However, a multiscale modeling framework covering all scales has not been fulfilled due to the incomplete coupling strategies. This study develops a multiscale model coupling all five scales. The elementary reaction path is derived from first-principles calculation, which is applied to a dual-site mean-field microkinetics describing the states of active site pairs; bulk-phase ion diffusion is treated by a lumped parameter method considering the asymmetrical effects of different site types. The intrinsic reaction kinetics is coupled with intraparticle gas diffusion and fluidization computed via CFD–DEM; experimental validation is conducted on a micro-fluidized-bed thermogravimetric analyzer measuring the solid conversion. The model is applied to the reduction of CaMn0.375Ti0.5Fe0.125O3−δ by H2 at designed gas concentrations and temperatures, revealing the effects of parameters from all scales on the overall reaction kinetics. The developed multiscale framework can be further adopted in other heterogeneous reactions with determined solid microstructures.